Sustainable Tourism Development in The Development of Pontianak Equator Weaving Tourism Village - Annisa Rizqa Alamri; Nunung Nurwati; Yayang Aristy; Olivia Rovince Purba; Dhea Frastika; Zainal Fadri (Alfuad: Jurnal Sosial Keagamaan, 2023)
This research aims to analyze more deeply the development of a weaving tourism village in Pontianak City. The method used in this research is descriptive qualitative data collection techniques using in-depth interviews and literature studies, where metadata is taken from books, online journals, and secondary references related to this research. This research was analyzed using sustainable tourism development. The results of the study found that the development of the equator weaving village has paid attention to economic, ecological, and social aspects so that the equator weaving village can become one of the booming tourism village pilots in Pontianak City.